2007
DOI: 10.1021/ja072697v
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Reduced Ruthenium Nanoparticles as a Highly Active Heterogeneous Catalyst for Hydrogenation of Monoaromatics

Abstract: We report here a thermal reduction method for preparing Ru catalysts supported on a carbon substrate. Mesoporous SBA-15 silica, surface-carbon-coated SBA-15, templated mesoporous carbon, activated carbon, and carbon black with different pore structures and compositions were employed as catalyst supports to explore the versatility of the thermal reduction method. Nitrogen adsorption, X-ray diffraction, field-emission scanning electron microscopy, transmission electron microscopy, scanning transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 92 publications
3
110
0
Order By: Relevance
“…57,60 All MnO 2 -carbon composites present a weight loss of approximately 6% between room temperature and 150…”
Section: Xrd Characterization-mentioning
confidence: 99%
“…57,60 All MnO 2 -carbon composites present a weight loss of approximately 6% between room temperature and 150…”
Section: Xrd Characterization-mentioning
confidence: 99%
“…Recently, Su et al [210] reported a simple thermal reduction method for preparing Ru NPs supported on mesoporous SBA silica, surface-carbon-coated SBA or templated mesoporous carbon. The Ru NPs exhibited good dispersion and resistance against oxidation, lack of aggregation and pore blocking, and less leaching.…”
Section: Nps Supported On Metal Oxides or Carbon Supportsmentioning
confidence: 99%
“…It is a low-cost material than that of Pd and Pt. Ruthenium nanoparticles were used in many applications such as catalytic dehydrogenation [3], methanol fuel cells [4], synthesis of diesel fuels [5], azo dye degradation [6], removal of organic pollutants from water [7] and so on. Synthesis of Ru NPs is usually carried out by various physical and chemical methods such as microwave irradiation [6,8], sonochemical method [9], hydrothermal method [10] and electrochemical method [11].…”
Section: Introductionmentioning
confidence: 99%